Service Delivery in Fragile and Conflict-Affected States - Baird, Mark (Washington, DC: World Bank, 2012)
Finds fragile and conflict-affected (FCA) states experience poor delivery of basic services which include: (1) social services such as health, education, clean water, and sanitation; (2) social protection ranging from social safety nets to livelihood enhancing programs; and (3) security and justice. Using the framework from the 2004 WDR on Making Services Work for Poor People, which summarizes the accountability relationships between policy makers (and politicians), service providers, and citizens (especially the poor), and the framework proposed in the Concept Note for the 2011 WDR, the following conclusions are reached: the political and institutional context of each FCA state exerts particular influence on results; the contribution of the private sector, NGOs, religious organizations, and community groups plays a vital role; the danger of stresses from conflict situations can cause a breakdown of delivery of social services; and strong leadership on the national, local, and tribal levels is the best way to address and respond to people's needs.